Evaluating the participation of an ethnic minority group in informal employment: a product of exit or exclusion?. Issue 4 (2nd October 2017) - Shahid, Muhammad Shehryar; Rodgers, Peter; Williams, Colin C.
Abstract: This paper critically evaluates competing explanations for the participation of ethnic minority groups in informal employment. These interpret their participation either through a structuralist lens arising out of 'exclusion' from formal employment or through a neo-liberal and/or post-structuralist lens driven by voluntary 'exit' from formal institutions. To evaluate critically these competing explanations, this paper reports a survey of the experiences of Pakistani immigrants in informal employment in Sheffield, including fifty face-to-face interviews and two focus groups. The findings highlight informal employment amongst this Pakistani ethnic minority group is neither universally driven by exclusion nor exit. Instead, some participate mostly due to exclusion, others mostly for exit rationales and some for a combination of the two, with different mixtures across different groups and types of informal employment. The outcome is a call for greater appreciation of the multifarious character of undeclared work and a move beyond simplistic explanations and policy responses.